THE INFLUENCE OF ONLINE CUSTOMER REVIEW AND PERCEIVED PRICE OF JIMSHONEY PRODUCTS IN DUREN SAWIT - Nurlehu, Ikra Salma (Kinerja, 2025)
This study aims to determine the influence of Online Customer Review and Perceived Price on Purchase Intention of Jimshoney Products in Duren Sawit. This quantitative study involved 120 respondents. The analytical methods used include validity, reliability, normality, multicollinearity, heteroscedasticity tests, multiple linear regression, correlation, coefficient of determination, and hypothesis testing. The t-test results showed that Online Customer Review did not significantly affect Purchase Intention, with a t-count < t-table (-0.813 < 1.98045) and a significance value > 0.05 (0.418). Meanwhile, Perceived Price had a significant effect on Purchase Intention, with a t-count > t-table (8.713 > 1.98045) and a significance value < 0.05 (0.000). The correlation value of 0.662 indicates a strong relationship among the studied variables. The coefficient of determination (43.8%) shows that Purchase Intention is influenced by Online Customer Review and Perceived Price, while the remaining 56.2% is influenced by other factors not examined in this study. This research contributes to the development of marketing science by emphasizing the significance of perceived price in shaping consumer purchase intention and offering insights into consumer behavior dynamics in the local e- commerce.